JAK2-STAT Epigenetically Regulates Tolerized Genes in Monocytes in the First Encounter With Gram-Negative Bacterial Endotoxins in Sepsis - Morante-Palacios, Octavio; Lorente-Sorolla, Clara; Ciudad, Laura; Calafell-Segura, Josep; Garcia-Gomez, Antonio; Català-Moll, Francesc; Ruiz-Sanmartín, Adolfo; Martínez-Gallo, Mónica; Ferrer, Ricard; Ruiz-Rodriguez, Juan Carlos; Álvarez-Errico, Damiana; Ballestar, Esteban (Frontiers in Immunology, 2021)
Microbial challenges, such as widespread bacterial infection in sepsis, induce endotoxin tolerance, a state of hyporesponsiveness to subsequent infections. The participation of DNA methylation in this process is poorly known. In this study, we perform integrated analysis of DNA methylation and transcriptional changes following in vitro exposure to gram-negative bacterial lipopolysaccharide, together with analysis of ex vivo monocytes from septic patients. We identify TET2-mediated demethylation and transcriptional activation of inflammation-related genes that is specific to toll-like receptor stimulation. Changes also involve phosphorylation of STAT1, STAT3 and STAT5, elements of the JAK2 pathway. JAK2 pathway inhibition impairs the activation of tolerized genes on the first encounter with lipopolysaccharide. We then confirm the implication of the JAK2-STAT pathway in the aberrant DNA methylome of patients with sepsis caused by gram-negative bacteria. Finally, JAK2 inhibition in monocytes partially recapitulates the expression changes produced in the immunosuppressive cellular state acquired by monocytes from gram-negative sepsis, as described by single cell-RNA-sequencing. Our study evidences both the crucial role the JAK2-STAT pathway in epigenetic regulation and initial response of the tolerized genes to gram-negative bacterial endotoxins and provides a pharmacological target to prevent exacerbated responses.